2022
DOI: 10.1056/nejmoa2111815
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Mini-Slings for Stress Urinary Incontinence in Women

Abstract: BACKGROUNDUntil recently, synthetic midurethral slings (made of mesh or tape) were the standard surgical treatment worldwide for female stress urinary incontinence, if conservative management failed. Data comparing the effectiveness and safety of newer single-incision mini-slings with those of standard midurethral slings are limited. METHODSWe performed a pragmatic, noninferiority, randomized trial comparing minislings with midurethral slings among women at 21 U.K. hospitals during 36 months of follow-up. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…Transparent multicentre trials independent from industry are fundamental to more adequately establish the benefit of modern surgical techniques and move beyond this impasse. Consistent with previous trials in the spinal 55 and non‐spinal 56 , 57 , 58 literature, these trials should be independent from industry and be supported by philanthropic and governmental research funding agencies. In a similar vein, the methodological flaws and systemic biases present within the existing literature must be acknowledged.…”
Section: Limitations Of the Spinal Surgery Literaturesupporting
confidence: 68%
“…Transparent multicentre trials independent from industry are fundamental to more adequately establish the benefit of modern surgical techniques and move beyond this impasse. Consistent with previous trials in the spinal 55 and non‐spinal 56 , 57 , 58 literature, these trials should be independent from industry and be supported by philanthropic and governmental research funding agencies. In a similar vein, the methodological flaws and systemic biases present within the existing literature must be acknowledged.…”
Section: Limitations Of the Spinal Surgery Literaturesupporting
confidence: 68%
“…The literature review initially yielded 1750 articles. After removing duplicates and screening studies based on their titles and abstracts, seventeen [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] studies were found, including retrospective and prospective ones. Comparative studies comprised the entirety of those included in this meta-analysis.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…This collection of articles spans the years 2011 through 2023. Six of the seventeen articles were observational cohort studies [20,[22][23][24]26,27], and the other eleven were controlled trials [13][14][15][16][17][18][19]21,25,28,29]. Of the eleven controlled trials, nine were randomized controlled trials (RCTs), one was a controlled clinical trial (CCT) [18], and one was a quasi-randomized trial [15].…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations